Hyperkeratotic Verrucous Porokeratosis - Rao Mummidi Venkateswara; Singh Ajit; Thappa Devinder Mohan; Ratnakar Chaganti (Wolters Kluwer Medknow Publications, 1998)
A 40 year old male having porokeratosis of mibelli with its rare variant, hyperkeratotic verrucous porokeratosis, is reported here.